High ideals: the misappropriation and reappropriation of the heroic label in the midst of a global pandemic. Issue 3 (16th February 2021) - Kinsella, Elaine L.; Sumner, Rachel C.
Abstract : The purpose of this article is to offer an alternative, more nuanced analysis of the labelling of frontline workers as heroes than originally proposed. Here, we argue that the hero narrative in itself need not be problematic, but highlight a number of wider factors that have led to the initial rise (and subsequent fall) in support for labelling frontline workers as heroes. Through our related work, we have gathered similar stories from frontline workers where they feel betrayed, let down or otherwise short-changed by the hero label, and we have sought to make sense of this through understanding more about how the hero label is used rather than what it means. In this article, we propose a way forward where there is greater discussion around the hero label in this context where individuals can be heroes but still struggle, still fail and still feel vulnerable, and where heroism is viewed as a state of interdependence between heroic actor and the wider group. It is true that heroes can inspire, lead, guide and build morale and camaraderie, but collective responsibility is held with us all. We can draw hope and energy from our heroes, but we must dig deep and be proactive, particularly in the face of adversity. In doing so, we support the heroes to lead from the front and ensure that even though we cannot physically help; we are not making their situation worse.